Developing Methematics Student Activitu Sheel (SAS) In transfornation for Seventh Grade Students of SMP/MTs Based Curriculum 2014 - Aini, Noor; Sumargiyani, Sumargiyani (Universitas Papua, 2018)
This research aims to produce teaching materials in the form of Student Activity Sheet (SAS) in transformations for students of class VII SMP/MTs based curriculum 2013 and to test the feasibility of SAS in mathematics learning. This research is a development with the steps of Research and Development (R&D) of the ADDIEÂ Â model (Analysis, Design, Development, Implementation, Evaluation). The research is carried out at SMP N 1 Prambanan Sleman and SMPN 4 Kalasan, Sleman. The research data is obtained from the questionnaire evaluation media matter by media matter experts, questionnaire evaluation media by media experts, questionnaire evaluation student responses by students. The research data are analyzed by the process of descriptive analysis and the process of analysis questionnaire with Likert scale. The results showed that the SAS of mathematics developed are good quality with an average percentage of ideals 82,416% and validity criteria by 67,999% < ð‘‹ â‰¤ 83,998%.Â DOI:Â Â https://doi.org/10.30862/jhm.v1i1.804